Sketches of the life of Mgr. de Mazenod, Bishop of Marseilles, and founder of the Oblates of Mary Immaculate [electronic resource] : and of the missionary labours and travels of members of that society in Canada, Labrador, the Red River regions, Saskatchewan, on the borders of the Great Slave and Great Bear Lakes, in the Mackenzie regions, to the confines of the Arctic Ocean, and in British Columbia - Cooke, Robert, 1820?-1882 (London : Burns & Oates; Dublin : M.H. Gill, 1879)
Part of a CIHM set. For individual microfiches in this set see CIHM microfiches nos. 06464-06466. "Vol. I." Electronic reproduction. Mode of access: Internet. 44